Preparation And Characterization Of Gelam Wood And Rice Husk Activated Carbons For Thin Layer Chromatography Stationary Phase - Kumar Jayaram, Sarabanan (2002)
Gelam wood (Meleuca Cajiputi) was used as a precusor for the preparation of activated carbon. Potassium orthophosphate, potassium hydroxide , phosphoric acid and carbon-dioxide were used as chemical and physical activating agents. The industrial activated carbons AC (7080 and 4050) were used as comparison. In addition physically activated carbon of rice husk was also used in this study. Thirty grams of shredded gelam wood were impregnated with 9% w/w K3P04, for the potassium hydroxide impregnation 9% w/w KOH was impregnated with thirty grams of wood. 2. 2 M H 3P04 concentration of phosphoric acid was used for the impregnation of thirty grams of gelam wood.Then the impregnated wood was carbonized in a horizontal electric furnace. The activated carbons were washed using 1.0 M nitric acid followed by distilled water using reflux method.Surface area, functional group analysis, elemental analysis, pH effect, moisture and ash content are some of the characterization methods done on the activated carbons. The study of the surface morphology was done using the scanning electron microscope. Elemental constituents of the activated carbons was done using atomic absorption analysis. The atomic absorption spectra showed that Ca, K, Mg, Zn, Pb and Fe were present m the activated carbons.